A VLES AND TWO-WAY DYNAMIC FLUID-STRUCTURE INTERACTION STUDY OF WIND TURBINES - Sarsenov, Erkhan (School of Engineering and Digital Sciences, 2023)
From year to year the energy demand is rising worldwide, which is leading to the development of renewable energy sources. One of them are the wind turbines that generate energy from the wind. However, in order to meet the energy demand and increase the efficiency, they are being made larger and larger, which is causing serious issues such as noise and vibration, as well as difficulties in studying their aerodynamics. Therefore, there is a need for Fluid-Structure Interaction (FSI) analysis of wind turbines, which can be useful in solving these problems and optimal design of the turbines. There are two methods of FSI analysis implemented in this work, high-fidelity and low-fidelity. The first method aimed to create a 2-way dynamic FSI of wind turbines with the application of the advanced VLES turbulence model. The FSI was tried to be performed by the coupling of the CFD and CSD solvers in preCICE software using the Arbitrary Eulerian Lagrangian (ALE) approach. The second method is done by coupling the Lifting Line Free Vortex Wake aerodynamic solver with the Chrono structural solver in QBlade software. The whole software setup was done, including the connection between solvers, dependencies as well as the test cases. However, the first method had some limitations, which were shown and explained. The findings and results are presented and discussed in the paper.
Keywords: type of access: open access; Two-Way Dynamic Fluid-Structure Interaction Study; Wind Turbines; VLES